Adverse Drug Reactions in Multidrug-resistant Tuberculosis Patients on Longer Bedaquiline-based Regimen at a Tertiary Care Center in Mumbai - Abhishek Saini; Snehal Jadhav (Journal of Advanced Lung Health)
Background: Multidrug-resistant tuberculosis (MDR-TB) has remained a major global public health concern over the years due to the morbidity and mortality associated with the disease. The prolonged duration of drug treatment and adverse drug reactions (ADRs) may affect the compliance and eventually the treatment outcome. Aim: The aim of this study was to determine the frequency of ADRs in patients during treatment of MDR-TB. Materials and Methods: We retrospectively reviewed the medical records of the patients diagnosed with MDR-TB during May 2021 to June 2022 and completed their treatment by December 2023 at the respiratory medicine outpatient department of a tertiary care hospital, Mumbai. We enrolled 169 patients treated with all oral longer bedaquiline-based regimens under programmatic condition. The data regarding demography, drug-resistant pattern, and ADRs were recorded. ADRs were evaluated for onset, causality assessment, severity assessment, and measures required to alleviate them. Results: Among a sample size of 169 patients, 60 (35.50%) patients developed a total of 106 ADR during the treatment. These ADRs were categorized into 10 types. In 37 patients out of 60 (61.66%), more than 1 ADR were observed during the treatment. The incidence of ADRs among females was higher 43 (25.44%) than males 17 (10%). All patients developed ADR after 2 months of treatment initiation. Among the ADRs, the most commonly observed were peripheral neuropathy 32 (30.18%), followed by nausea and vomiting 21 (19.8%). The 39 (36%) serious ADRs observed lead to the omission of offending drug. Conclusion: Our study included 10 types of ADRs with peripheral neuropathy as the most common, followed by nausea and vomiting. Majority of ADRs were mild, had a probable relationship with the offending drug, and were manageable. ADRs were mostly associated with linezolid.